An Interactive Procedure to Preserve the Desired Edges during the Image Processing of Noise Reduction. (4th May 2010) - Hsu Hsu, Chih-Yu Chih-Yu; Huang Huang, Hsuan-Yu Hsuan-Yu; Lee Lee, Lin-Tsang Lin-Tsang
Abstract : The paper propose a new procedure including four stages in order to preserve the desired edges during the image processing of noise reduction. A denoised image can be obtained from a noisy image at the first stage of the procedure. At the second stage, an edge map can be obtained by the Canny edge detector to find the edges of the object contours. Manual modification of an edge map at the third stage is optional to capture all the desired edges of the object contours. At the final stage, a new method called Edge Preserved Inhomogeneous Diffusion Equation (EPIDE) is used to smooth the noisy images or the previously denoised image at the first stage for achieving the edge preservation. The Optical Character Recognition (OCR) results in the experiments show that the proposed procedure has the best recognition result because of the capability of edge preservation.